A survey on recent research in business intelligence. Issue 6 (7th October 2014) - Aruldoss, Martin; Lakshmi Travis, Miranda; Prasanna Venkatesan, V.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Business intelligence (BI) has been applied in various domains to take better decisions and it provides different level of information to its stakeholders according to the information needs. The purpose of this paper is to present a literature review on recent works in BI. The two principal aims in this survey are to identify areas lacking in recent research, thereby offering potential opportunities for investigation. Design/methodology/approach – To simplify the study on BI literature, it is segregated into seven categories according to the usage. Each category of work is analyzed using parameters such as purpose, domain, problem identified, solution applied, benefit and outcome. Findings – The BI contribution in various domains, ongoing research in BI, the convergence of BI domains, problems and solutions, results of congregated domains, core problems and key solutions. It also outlines BI and its components composition, widely applied BI solutions such as algorithm-based, architecture-based and model-based solutions. Finally, it discusses BI implementation issues and outlines the security and privacy policies adopted in BI environment. Research limitations/implications – In this survey BI has been discussed in theoretical perspective whereas practical contribution has been given less attention. Originality/value – A comprehensive survey on BI which identifies areas lacking in recent research and providing potential opportunities for investigation.